Correlation Between The History of Previous Lower Extremity Amputation as a Risk Factor for the Subsequent Lower Extremity Amputation in Diabetic Patients Among RSUD Dr. Soetomo Patients in 2018 - Mochamad Wildan; Sony Wibisono; Heroe Soebroto (Health Notions, 2020)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia. Complications are common among patients with this condition, such as diabetic foot syndrome, which is the presence of foot ulcer associated with neuropathy, PAD, and infection, and is a major cause of LEA. Aim of this research is to analyze the correlation between previous LEA as a risk factor for the subsequent LEA in patients with Diabetic Foot among patients in RSUD Dr. Soetomo, Surabaya from January-December 2018. This is descriptive cross-sectional study. Data was analyzed using descriptive statistic and correlation test with Microsoft Excel 2007 and SPSS 20. Statistical testing was performed using Spearman’s rank correlation and Cohen J criteria with significance level of P55 years old (62.9%). Mostly have undergone LEA (74.3%) while the remaining have undergone LEA twice (17.1%). There is a significant correlation between initial LEA and the subsequent LEA (p0.01). Keywords: diabetes mellitus; lower extremity amputation; risk factors; RSUD Dr. Soetomo